AN APPROACH OF IMPROVING ARCHITECTURE STUDENTS’ ENGLISH VOCABULARY - G’ofurova Sarvara Madaminjonovna; Kuchkarova Ozodaxon Abakulovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses an approach of improving architecture students’ English vocabulary during teaching English in classroom. The importance of teaching English for professional uses and particularly in the field of architecture is undeniable. English proficiency is required in all professional areas but it becomes essential in the architecture because of its specific characteristics.